Efficacy of Melatonin and Pentoxifylline combination therapy in treatment of endotoxin induced hepatic dysfunction in white albino mice - Ammara Khan, Ammara Khan; Ayesha Afzal, Ayesha Afzal; Zahid Azam Chaudhry, Zahid Azam Chaudhry; Samia Rafique, Samia Rafique (Journal of Rawalpindi Medical College, 2022)
Introduction: Despite major expansion and elaboration in treatment protocols of septic patients, mortality rate is still very high due to multiple organ damage including hepatotoxicity. We in study evaluated the role of two strong anti-inflammatory agents, melatonin and pentoxifylline, as a combined treatment in lipopolysaccharide induced hepatic dysfunction in white albino mice. Material and Methods: Endotoxemia was reproduced in white albino mice through intraperitoneal administration of lipopolysaccharide (LPS) of serotype E.Coli. Therapeutic potential of the both melatonin and pentoxifylline alone and as combined therapy was adjudged by administering agents 2 hours after LPS delivering. The extent of liver damage was evaluated via serum alanine aminotransferases (ALT) and aspartate aminotransferase (AST) estimation along with histopathological examination of liver tissue. Results: Lipopolysaccharide administration (Group 2) resulted in marked hepatotoxicity as evident by statistically raised serum ALT ((p≤0.01) and AST (p≤0.01) at the end of experimentation. Also liver cross section examination showed marked distortion of liver parenchyma. Melatonin (Group 3) was prosperous in aversion of LPS invoked hepatotoxicity as proved by lessening of augmented ALT (p≤0.01) and AST (p≤0.01) along with restoration of pathological changes on liver sections (p≤0.05). Pentoxifylline generated similar results and serum ALT, AST and histological alteration abated considerably (p≤ 0.05).Combination therapy in animals of Group 5 also tapered LPS evoked hepatic dysfunction statistically considerably. Conclusion: Melatonin and pentoxifylline alone and as combination therapy as effective in countering LPS induced hepatotoxicity. However the combination therapy did not yield synergistic effects. Keywords: Lipopolysaccharides, Endotoxin, Hepatotoxicity, Melatonin, Pentoxifylline.